Sabah Traditional Medicine Database and Application: SabahTMed - Aslina Baharum; Rozita Ismail; Noor Fzlinda Fabeil; Nur Shahida Ab Fatah; Rozita Hanapi (2018)
Nowadays, android technology and smartphone become one of the most important devices in society. The application of this technology is vast and easy to use. Currently, there are limited or maybe none android application developed related to Sabah Traditional Medicine. The development of this application hopefully will help the local people to identify remedy nearby, especially in an emergency situation or other alternative way to cure their disease without relying to the hospital medication. Therefore, this paper proposed a Web-based and Mobile (android) application to help user to find information about traditional medicine found in Sabah. Hopefully, this application could help users to identify traditional medicine that can be found in the Sabah including its name, local name, and instruction on how to use it, and images to help them identify the remedy. A few expertises were chosen to validate the data collection where they are expert and practitioner of traditional medicine in Sabah.